2019
DOI: 10.48550/arxiv.1910.12161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Nonlocal Transport Equation Modeling Complex Roots of Polynomials under Differentiation

Abstract: Let pn : C → C be a random complex polynomial whose roots are sampled i.i.d. from a radial distribution u(r)rdr in the complex plane. A natural question is how the distribution of roots evolves under repeated (say n/2−times) differentiation of the polynomial. We derive a mean-field expansion for the evolution of ψ(s) = u(s)sWe discuss some numerical examples suggesting that this particular solution may be stable. We prove that the solution is linearly stable. The linear stability analysis reduces to the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Additionally, the analogous 'infinite degree' setting, in which polynomials are replaced by analytic functions, has also been considered -see Polya [34], Farmer & Rhoades [13] and Pemantle & Subramanian [33]. Another natural extension is to consider the dynamics of the roots of successive derivatives for complex-valued polynomials p n : C → C. If the roots are given by a smooth probability distribution u(0, z) : C → R ≥0 and the limiting measure u(0, z) is radial, O'Rourke & Steinerberger [31] suggest that the following nonlocal transport equation…”
Section: Related Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the analogous 'infinite degree' setting, in which polynomials are replaced by analytic functions, has also been considered -see Polya [34], Farmer & Rhoades [13] and Pemantle & Subramanian [33]. Another natural extension is to consider the dynamics of the roots of successive derivatives for complex-valued polynomials p n : C → C. If the roots are given by a smooth probability distribution u(0, z) : C → R ≥0 and the limiting measure u(0, z) is radial, O'Rourke & Steinerberger [31] suggest that the following nonlocal transport equation…”
Section: Related Resultsmentioning
confidence: 99%
“…The derivation was, however, based on heuristic arguments, a rigorous proof is still outstanding. It was recently shown [44] that there are an infinite number of conservation laws that are satisfied by both explicit closed form solutions, indicating that the PDE might have an abundance of interesting structure (see also [16,31]). (3) The case t = 1.…”
mentioning
confidence: 99%
“…The same question is meaningful for general polynomials p n : C → C having a distribution of roots being given by a smooth probability distribution u(0, z) : C → R ≥0 in the complex plane. In case the limiting measure u(0, z) is radial, the problem was studied by O'Rourke and the author [23] who (non-rigorously) derived a nonlocal transport equation…”
Section: A Partial Differential Equationmentioning
confidence: 99%
“…Polynomials. Roots of polynomials are a classical subject and there are many results we do not describe here, see [6,7,8,12,13,16,17,18,19,20,24,26,27,28,29,30,31,32,33,34,37,38,39,40]. Our problem will be as follows: let µ be a compactly supported probability measure on the real line and suppose x 1 , .…”
mentioning
confidence: 99%
“…Numerical simulations in [15] also suggested that the solution tends to become smoother. O'Rourke and the author [29] derived an analogous transport equation for polynomials with roots following a radial distribution in the complex plane.…”
mentioning
confidence: 99%